Lutein inhibits glutamate-induced apoptosis in HT22 cells via the Nrf2/HO-1 signaling pathway - Li, Zhenhua; Cao, Zhuohua; Chen, Fangmei; Li, Bin; Jin, Hanyong (Frontiers in Neuroscience, 2024)
Excessive glutamate levels induce oxidative stress, resulting in neuronal damage and cell death. While natural antioxidants show promise for neuroprotection, their effectiveness in the central nervous system (CNS) is limited by the blood-brain barrier. Lutein, a neuroprotective carotenoid, has gained attention for its ability to traverse this barrier and accumulate in various brain regions. However, the specific neuroprotective effects of lutein on hippocampal neurons have not been extensively explored before our investigation. This study aimed to elucidate the mechanisms underlying the protective effects of lutein against glutamate-induced cell death in HT22 cells. Our results demonstrate that lutein effectively attenuated glutamate-induced apoptosis due to its antioxidant properties. Additionally, lutein inhibited glutamate-induced mitochondrial-mediated apoptosis. We observed that lutein modulated the nuclear translocation of nuclear factor erythroid 2related factor 2 (Nrf2) and upregulated the expression of heme oxygenase-1 (HO-1). Inhibition of HO-1 by tin protoporphyrin (SnPP), a synthetic inhibitor, weakened the protective effect of lutein. Furthermore, we demonstrated that lutein prevented the aberrant activation of MAPKs induced by glutamate, including ERK1/2, p38, and JNK, thereby conferring oxidative protection. In conclusion, our study highlights the potent antioxidant properties of lutein, which effectively safeguards against glutamate-induced mitochondrial apoptotic cell death through the Nrf2/HO-1 signaling pathway and inhibition of MAPK activation. These findings demonstrate that lutein exerts a neuroprotective effect against glutamate-induced neuronal cell damage.